Virtual reality on the WWW: simulating class I procedures in restorative dentistry - Faisal Mohamed, Nur Fadziana; Luke, D.A. (2002)
The World Wide Web (WWW) is a very efficient way for information exchange.Advancement in Web technology now permits visualisation software to be shared across the Internet. This paper discusses the design and prototype development of a Web-based VR to create an interactive-simulation for the procedure of a Class I cavity preparation in restorative dentistry. The aim of this research is to find out whether a simple solution utilising the wide accessibility of the WWW would be feasible to provide a portable, scalable and low-cost real time dental simulation.To achieve this, a virtual reality simulator, containing simulations of the Class I restorative equipment and materials, is embedded in the Web page.The requirements of a Web based VR simulation for this type of application are also discussed.